2017
DOI: 10.1007/978-3-319-49763-1_5
|View full text |Cite
|
Sign up to set email alerts
|

A Stronger Derived Torelli Theorem for K3 Surfaces

Abstract: In an earlier paper the notion of a filtered derived equivalence was introduced, and it was shown that if two K3 surfaces admit such an equivalence then they are isomorphic. In this paper we study more refined aspects of filtered derived equivalences related to the action on the cohomological realizations of the Mukai motive. It is shown that if a filtered derived equivalence between K3 surfaces also preserves ample cones then one can find an isomorphism that induces the same map as the equivalence on the coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The moduli theory of twisted sheaves for complex K3's was initiated by S. Mukai and its generalization to positive characteristic has been studied by Lieblich, Maulik, Olsson and Snowden (c.f. [20], [21], [22]). Huybrechts has shown that in fact, over C, every isogeny can be realized by a sequence of such operations [13, Theorem 0.1].…”
Section: S (Cspin(l D ) ω)mentioning
confidence: 99%
See 1 more Smart Citation
“…The moduli theory of twisted sheaves for complex K3's was initiated by S. Mukai and its generalization to positive characteristic has been studied by Lieblich, Maulik, Olsson and Snowden (c.f. [20], [21], [22]). Huybrechts has shown that in fact, over C, every isogeny can be realized by a sequence of such operations [13, Theorem 0.1].…”
Section: S (Cspin(l D ) ω)mentioning
confidence: 99%
“…We remark that in fact any two supersingular K3 surfaces X, X ′ over Fp for p > 2 are isogenous according to our definition, as Pic (X) Q ∼ = Pic (X ′ ) Q as Q-quadratic lattices. By works of Artin and Radukov-Shafarevich, for any supersingular X over Fp , Pic (X) ∼ = N p,σ for some 1 ≤ σ ≤ 10, where N p,σ is the unique even, non-degenerate Z-lattice with signature (1,21) and discriminant group (Z/pZ) 2σ . One may check that N p,σ ⊗Q ∼ = N p,σ ′ ⊗Q for any two different σ, σ ′ by the Hasse principle: N p,σ ⊗R ∼ = N p,σ ′ ⊗R as a real quadratic form is determined by its signature.…”
Section: Constructing Liftingsmentioning
confidence: 99%
“…We also point out here that the proofs of these results go via lifting to characteristic zero and thus use the Hodge theoretic description given by Mukai and Orlov. Furthermore, Lieblich-Olsson [46] also proved the derived version of the Torelli theorem using the Crystalline Torelli theorem for supersingular K3 surfaces.…”
Section: Introductionmentioning
confidence: 96%
“…This explains why the conclusions of Theorem 1.2 and [BM,Theorem 5.1] are not completely symmetric. Finally, we point out that filtered equivalences have been introduced in [LibO1], together with other stronger versions in [LibO2], to establish a derived version of Torelli theorem for K3 surfaces in characteristic p = 2. Now we go back to the proof of Theorem 1.1.…”
Section: Introductionmentioning
confidence: 99%